Teachers’ Attitudes in Conducting the Formative Assessment on Students’ Speaking Competence - Gautami, Gusti Ayu Agung Tania; Sulistia Dewi, Dr. Ni Luh Putu Eka; Paramartha, Anak Agung Gede Yudha (Universitas Pendidikan Ganesha, 2022)
Current online learning requires teachers to be proficient in using online-based assessments by looking at their students' progress in their speaking skills. Thus, this study aimed to investigate teachers' perception of the use of formative assessments in online learning of junior high school students' speaking competence. This research was conducted at two junior high schools located in Tejakula village. Seven English teachers were involved in the study. This research was mixed-method research by combining quantitative data and qualitative data. In this study, data collection was collected with questionnaires and in-depth interviews to obtain information about teachers’ perceptions. This research revealed that respondents have a positive attitude towards formative assessments in online learning towards students' speaking competence.